Pharmacometrics in tuberculosis - Peloquin, Charles A. (Henry Stewart Talks, 2014)
FDA approved drugs for tuberculosis, Non-FDA approved drugs for tuberculosis, How do antibiotics work?, Pharmacokinetics and pharmacodynamics, Pharmacodynamics of isoniazid and ethionamide, "Concentration dependent" antimicrobials, Concentration dependent activity of rifampin, Concentration dependent activity of isoniazid and rifabutin